PERSEPSI SISWA DALAM MELANJUTKAN PENDIDIKAN TINGGI DI BIDANG MARITIM PADA ERA DIGITAL - Tri Cahyadi; Darul Prayogo; Damar Isti Pratiwi; Taruga Runadi (Institut Pendidikan Tapanuli Selatan, 2024)
The present study aimed to investigate students’ perception in pursuing maritime higher education in digital era. It involved 72 students from 3 different majors in an Indonesian maritime higher education. This study used a quantitative research design which was facilitated by a survey questionnaire to gather the data. The questionnaire was in the form of 5-Likert scale consisting of 4 categories: education quality, economic motif, job availability, and self-competence. The data were analyzed using SPSS 25 employing Parametric tests analysis: descriptive statistics, Pearson r correlation, and Cohen d coefficient to find out the factors affecting students’ acceptance in continuing their degree in maritime higher education. The results showed that the students considered economic motif as the highest factor affecting their choice in pursuing higher degree in maritime sectors. Followed by job availability and self-competence, these factors became very important in competing toward professional maritime sectors. The lowest factor was education quality, yet the maritime higher education should keep up with improving maritime education quality as maritime industries developed fast in digital era. Some recommendations have been discussed to give insightful opinion for education policy makers and managerial board of maritime higher education institutions.